Motor unit remodelling in multifocal motor neuropathy: The importance of axonal loss. Issue 10 (October 2017) - Garg, Nidhi; Howells, James; Yiannikas, Con; Vucic, Steve; Krishnan, Arun V.; Spies, Judith; Bostock, Hugh; Mathey, Emily K.; Pollard, John D.; Park, Susanna B.; Kiernan, Matthew C.
Highlights: Axonal degeneration is an integral part of the disease process in MMN. Axonal loss in MMN may be masked by prominent re-innervation. Nerve conduction studies are not sensitive to motor unit remodelling in MMN. Abstract: Objective: To estimate the degree of axonal loss in patients diagnosed with multifocal motor neuropathy (MMN) using a novel assessment of motor unit numbers and size. Methods: Automated motor unit number estimation using a compound muscle action potential (CMAP) scan was undertaken in median nerves with conduction block. Results were compared with 30 age-matched healthy controls. Results: Compared with healthy controls, MMN patients had fewer motor units (MMN: 33 ± 11 vs HC: 93 ± 36 [mean ± SD]; p < 0.0001) and larger 'size of the largest unit' (MMN: 1.2 ± 0.5 mV vs HC: 0.4 ± 0.1 mV; p < 0.0001), despite having normal distal CMAP amplitudes (MMN: 7.6 ± 1.8 mV vs HC: 8.7 ± 2.5 mV; p = 0.24). Conclusions: MMN is associated with marked axonal loss which may be masked by striking re-innervation resulting in preservation of distal CMAP amplitudes. Significance: Assessment of motor unit properties should be incorporated into assessment of disease progression in MMN, given that nerve conduction studies are insensitive to motor unit remodelling.